“Integrasi Fikih dan Sains melalui Pembelajaran Berbasis Inkuiri dalam Kurikulum Merdeka Belajar” - Mahyarni Junida Nasution; Risnawati Risnawati; Alpizar Alpizar (Postgraduate, University of Mataram, 2026)
This study examines the integration of Fiqh and science through inquiry-based learning within the Merdeka Belajar curriculum at MTsN 1 Padang Lawas Regency, North Sumatra, Indonesia. A qualitative approach was employed using interviews, classroom observations, and document analysis to explore the implementation, benefits, and challenges of inquiry-based learning in Fiqh instruction. The findings reveal that inquiry-based learning is implemented through contextual problem stimulation, data collection from the Qur’an, Hadith, and other Islamic sources, collaborative discussions, presentations, and reflection. This approach transforms Fiqh instruction into a student-centered learning process, encouraging learners to construct knowledge through questioning, investigation, and critical reasoning. Integrating scientific perspectives enables students to connect Islamic legal principles with real-life issues, including health, hygiene, environmental sustainability, and social responsibility. As a result, students demonstrate improved critical thinking, conceptual understanding, learning autonomy, and collaboration. However, implementation is constrained by limited instructional time, varying student readiness, insufficient inquiry-based teaching materials, and restricted learning resources. Despite these challenges, inquiry-based learning effectively supports the objectives of the Merdeka Belajar curriculum by promoting independent learning, critical reasoning, and character development. Strengthening instructional design, teacher competence, and learning resources is essential for sustainable implementation in Islamic education